APPLICATION OF INDIVIDUAL COUNSELING WITH COGNITIVE DEFUSION TECHNIQUES TO OVERCOME FEELINGS OF INSECURITY IN ADOLESCENT VICTIMS OF BULLYING - Warni, Intan Setia; Razzaq, Abdur; Putra, Bela Janare (LP2M IAI Al-Khairat Pamekasan, 2024)
This study aims to evaluate the effectiveness of individual counseling using cognitive defusion techniques in reducing feelings of insecurity among bullied adolescents. Cognitive defusion, a component of Acceptance and Commitment Therapy (ACT), helps individuals change their response to negative thoughts. The research method used is quantitative with a quasi-experimental design, where 60 bullied adolescents were randomly divided into experimental and control groups. The experimental group received individual counseling sessions with cognitive defusion techniques for eight weeks, while the control group did not receive any intervention. Data on the level of insecurity were collected using the Insecure Feelings Scale (IFS) before and after the intervention. The results showed that the experimental group experienced a significant decrease in feelings of insecurity, with the average IFS score decreasing by 40% from 75 to 45. In contrast, the control group did not show significant changes in the IFS scores. Paired and unpaired t-tests indicated that this decrease was statistically significant (p < 0.001). These findings suggest that cognitive defusion techniques are effective in reducing feelings of insecurity among bullied adolescents. The practical implications of these findings are the importance of integrating cognitive defusion techniques into school counseling programs to help adolescents cope with the psychological impacts of bullying. Recommendations for future research include using a more rigorous research design with full randomization and exploring the long-term effects of this intervention in various cultural and geographical contexts.